Direct SW aerosol radiative forcing over Portugal - Santos, Dina (2012)
In this work, the evaluation of the aerosol radiative forcing at the top of the atmosphere as well as at the surface over the south of Portugal is made, particularly in the regions of Évora (38°34' N, 7°54' W) and of Cabo da Roca (38°46' N, 9°38' W), during years 2004 and 2005. The radiative transfer calculations, using the radiative transfer code Second Simulation of the Satellite Signal in the Solar Spectrum (6S), combine ground-based measurements, from Aerosol Robotic NETwork (AERONET), and satellite measurements, from MODerate Imaging Spectroradiometer (MODIS), to estimate the direct SW aerosol radiative forcing. The method developed to retrieve the surface spectral reflectance is also presented, based on ground-based measurements (AERONET) of the aerosol optical properties combined with the satellite-measured radiances (MODIS). The instantaneous direct SW aerosol radiative forcing values obtained at the top of the atmosphere are, in the majority of the cases, negative, indicating a tendency for cooling the Earth at the top of the atmosphere. For Desert Dust aerosols, over the Évora land region, the average forcing efficiency is estimated to be −25 Wm−2/AOT0.55 whereas for the Cabo da Roca area, the average forcing efficiency is −46 Wm−2/AOT0.55. In the presence of Forest Fire aerosols, both from short and long distances, the average value of forcing efficiency at the top of the atmosphere over Cabo da Roca is found to be −28 Wm−2/AOT0.55 and, over Évora, −27 Wm−2/AOT0.55. For specific situations, discussed in this work, the average surface direct SW aerosol radiative forcing efficiency due to the Desert Dust aerosols, in Évora region, is −66 Wm−2/AOT0.55, whereas in Cabo da Roca region, the corresponding average value is −38 Wm−2/AOT0.55. Considering the Forest Fire aerosols, over Évora region, the average surface direct SW aerosol radiative forcing efficiency can vary between −36 and −113 Wm−2/AOT0.55, the more negative value corresponding to forest fire aerosols coming only from shorter distances.